(Potency of Indonesian essential oils of non-exported commodities as sources of natural aroma chemical). - Sait, Salya (Balai Besar Industri Agro, 1992)
In search for the aroma industrial utilization of indonesia essential oils of non-exported commodities,yhe main chemical constituents of essential oils originated from the plant species of some cinnamomum,e.g. c.javanicum, c.camphora and c sintok,also foeniculum vulgare,hyptis suaveolens and ocimum canum,which are all grown likely in indonesia,were surveyed by literature.Based on criterion that the amount of each constituents present inthe oil must exceedÂ 10%, enantiomerically pure and harmless to man.it was found found that the cinnamomum species be likely the sources of safrole,whereas only foeniculum vulgare be likrly the source of fenchone.